Transformation Of Islamic Religious Education: An Analysis of The Implementation of the Independent Curriculum in Class VII SMPN 3 Pamekasan - Sayyi, Ach.; Gaffar, Abdul; Nisak, Shofiyatun (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2023)
This study aims to describe the implementation of the independent curriculum at SMPN 3 Pamekasan, especially in Islamic religious education. Qualitative approach. Case study type. Data were collected from the principal, curriculum vice principal, teachers, and students through observation, interviews, and documentation. Data were analysed with an interactive model and validated with various techniques. The results showed that the independent curriculum involves intracurricular, Pancasila learner profile strengthening projects, and extracurricular. The independent curriculum provides flexible, creative, and meaningful learning experiences and maintains the Pancasila learner profile. The independent curriculum also provides opportunities for students to develop academic and non-academic potential. The independent curriculum in Islamic religious education includes subjects such as Al-Qur'an and Hadith, Aqidah, Akhlak, and Fiqh. Implementing an independent curriculum involves continuous planning, implementation, and evaluation. The independent curriculum positively impacts students, teachers and schools but also requires support, commitment and further research.